(untitled) (Scientific journal of the Fergana State University, 2024)
A complex compound consisting of [Cd2(L)3(NO3)3∙(H2O)2](NO3)2 with 2-amino-1,3,4-thiadiazole and a Cd(II) salt was synthesized and a synthesis method was developed. The composition, structure and properties of the synthesized complex were analyzed using physicochemical methods: elemental analysis, IR spectroscopy, thermal analysis, X-ray diffraction analysis. The structure of the complex compound was studied by Hirshfeld surface analysis. The crystal structure parameters, hydrogen atoms bonded to the C atom, were calculated by X-ray diffraction analysis. The arrangement of the molecules of the complex compound in the plane and in the crystal cell was analyzed, and the structure of the compound was studied.